Managing Conversions Between Adobe CC and Microsoft Office. - Concepción, Anne-Marie (linkedin.com, 2016)
The exchange goes both ways with Creative Cloud and Office. Learn how to convert and share assets—text, graphics, chart data, and more—between Adobe CC and Microsoft Office.